Children with Congenital Hypothyroidism Have Similar Neuroradiological Abnormal Findings as Healthy Ones. (3rd October 2013) - Rachmiel, Marianna; Blaser, Susanne; Widjaja, Elysa; Rovet, Joanne
Abstract : Objective . To assess the neuroradiological findings of children with congenital hypothyroidism (CHT) compared to healthy controls (HC). Patients and Methods . Thirty children with CHT, mean age 12.5 ± 1.6 years, 14 (44.8%) males, were compared with 38 HC mean age 11.7 ± 1.7 years, 16 (45.7%) males. Clinical data were collected from medical charts and questionnaires seeking information on family history, birth and perinatal period events, medications, and overall health history. Neurocognitive function was assessed for global intelligence, visual and verbal memory, and executive functioning using standardized tests. Neuroimaging was performed using 1.5 T magnetic resonance imaging and assessed by two pediatric radiologists. Results . Children with CHT had a similar proportion of incidental findings as did the children in the HC group, at 43.3% and 39.5%, respectively, P = 0.69 . Abnormalities of the sellar region were reported in 13.3% of CHT group and 7.9% of HC group, P = 0.46 . Other incidental findings included cerebellar ectopia, choroidal fissure and pineal cysts, and multiple increased signal intensity foci. Neuroradiological findings were not associated with clinical and neurocognitive abnormalities. Conclusion . Neuroimaging of children with CHT demonstrated a similar incidence of structural abnormalities as in the healthy population. There is no association between those findings and neurocognitive function.